Relationship between HLA‐DPA1 genetic polymorphism and anembryonic pregnancy - Zhendong Wang; Xiaolin Lu; Xiuying Yao; Xinli Liu; Linlin Zhao; Shaoyan Chang; Ting Zhang; Bo Niu; Li Wang (Molecular Genetics & Genomic Medicine, 2020)
Abstract Background Human leukocyte antigen (HLA)‐DP is an HLA class II molecule. Overexpression of HLA class II molecules in placental trophoblast cells may induce pregnancy loss. However, the association between HLA‐DP and pregnancy loss remains unclear. HLA‐DPA1 is an HLA‐DP peptide chain. The objective of this study was to assess the association between HLA‐DPA1 genetic polymorphism and anembryonic pregnancy, a type of early pregnancy loss, in the Chinese population. Methods A case–control study was designed to compare the frequencies of HLA‐DPA1 gene polymorphisms in an anembryonic pregnancy group and a control group. Sixty‐eight cases and 122 controls were recruited. Statistical analysis was performed to assess the correlation between single‐nucleotide polymorphisms (SNPs) and anembryonic pregnancy susceptibility. MassARRAY high‐throughput DNA analysis was used to analyze 19 HLA‐DPA1 SNPs. To explore how HLA‐DPA1 polymorphism could affect anembryonic pregnancy, HLA‐DPA1 serum levels were analyzed by ELISA. Results Homozygous typing of rs1431403 (CC and TT) significantly increased the risk of anembryonic pregnancy in the case group (ORCC = 3.13, 95% CI: 1.50–6.53; ORTT = 2.96, 95% CI: 1.31–6.66; ORCC+TT = 3.06, 95% CI: 1.62–5.78). In samples with high HLA‐DPA1 levels (≥1,500 pg/ml), the homozygous rs1431403 genotypes (nCC = 21, 43.8%; nTT = 20, 57.1%) were observed more frequently than were heterozygous genotypes. Conclusion HLA‐DPA1 rs1431403 may be a risk factor for anembryonic pregnancy in the Chinese population. Homozygous rs1431403 genotypes (CC and TT) may increase the risk of anembryonic pregnancy by aberrantly increasing the HLA‐DPA1 levels.